2017
DOI: 10.1111/hae.13219
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies between the one‐stage clotting assay and the chromogenic assay in haemophilia B

Abstract: Our findings imply that assay discrepancy occurs for factor IX activity and that both type of assays are needed for a correct diagnosis and classification of haemophilia B. The underlying mechanism by which the mutation influences the assays remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 18 publications
1
41
1
Order By: Relevance
“…There is also a limitation in drawing conclusions about discrepancies when a single OSA is used as a “gold standard” in view of the known variability between different OSAs related to APTT reagent differences . Kilberg and colleagues recently reported discrepancies between CSA and OSA for measurement of native FIX in a subgroup of nonsevere Haemophilia B with FIX by CSA observed to be more than twice the OSA level . They speculated that this was related to a particular causative mutation.…”
Section: Discussionmentioning
confidence: 99%
“…There is also a limitation in drawing conclusions about discrepancies when a single OSA is used as a “gold standard” in view of the known variability between different OSAs related to APTT reagent differences . Kilberg and colleagues recently reported discrepancies between CSA and OSA for measurement of native FIX in a subgroup of nonsevere Haemophilia B with FIX by CSA observed to be more than twice the OSA level . They speculated that this was related to a particular causative mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in nonsevere hemophilia A have reported an assay discrepancy prevalence of 12% to 40% . Studies in hemophilia B are scarce, with 1 study demonstrating a prevalence of 25% assay discrepancy in a nonsevere hemophilia B population …”
Section: Diagnosis Of Nonsevere Hemophiliamentioning
confidence: 95%
“…In nonsevere hemophilia B, assay discrepancy was predominantly present with higher results with the chromogenic assay . The higher chromogenic assay results were found in patients with mutations p.Arg191His and p.Arg191Cys, located at the N‐terminal cleaving site of the linker protein domain.…”
Section: Diagnosis Of Nonsevere Hemophiliamentioning
confidence: 97%
“…In clinical practice, FIX activity assessment is most commonly performed using the aPTT‐based one‐stage assay (OSA) and less often the chromogenic assay . However, as for haemophilia A, both assays may be needed for an accurate diagnosis and classification of disease severity . The OSA is a simple and rapid method, which is inexpensive and easily automated, and is the established European Pharmacopeia method for FIX concentrate potency labelling .…”
Section: Assessment Of Clinical Heterogeneity and Treatment Response mentioning
confidence: 99%